Skrining Fungsi Ginjal dengan Estimasi Laju Filtrasi Glomerulus (eLFG) untuk Deteksi Dini Penyakit Ginjal Kronik - Shirly Gunawan; Alexander Halim Santoso; Bryan Anna Wijaya (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Chronic kidney disease (CKD) is a growing global health concern that frequently remains undiagnosed until advanced stages. Early detection through simple laboratory screening is essential to prevent disease progression and associated cardiometabolic complications. This community service program aimed to assess kidney function using serum creatinine and estimated glomerular filtration rate (eGFR), while increasing public awareness regarding CKD prevention. A total of 59 participants were included, with a mean age of 39.15 ± 15.39 years (range 16–75 years), predominantly female (74.58%). The mean serum creatinine level was 1.0 ± 0.19 mg/dL, and the mean eGFR was 91.08 ± 20.53 mL/min/1.73 m². Most participants demonstrated normal kidney function (28.8%) or mild decline (21.6%). A progressive reduction in eGFR with increasing age was observed, reflecting the physiological decline in nephron mass and renal perfusion. The program also provided education on kidney-protective practices, including optimal blood pressure control, diabetes management, adequate hydration, and avoidance of nephrotoxic agents. This intervention improved participants’ understanding of CKD risk factors and the importance of regular screening. In conclusion, serum creatinine and eGFR evaluation offer simple, accurate, and practical tools for early CKD detection, supporting promotive–preventive strategies to slow disease progression and enhance quality of life in at-risk populations.